Sensitivity enhancement in flame atomic absorption spectrometry for determination of copper in human thyroid tissues - Yaman, M; Akdeniz, I (Japan Soc Analytical Chemistry, 2004)
Various designs of quartz tube in a slotted tube atom trap were examined for improving the sensitivity of flame AAS. A 3.5-fold enhancement in the sensitivity was obtained by using the optimized method. The method was applied to the determination of Cu in cancerous and non-cancerous human thyroid tissues. The Cu concentrations of the cancerous samples tended to increase compared with the non-cancerous samples. Zn concentrations of the same tissues were also determined.
Keywords: Superoxide-Dismutase; Lead; Cadmium; Fruits; Soils; Zinc; Speciation